Brake disc with surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating and preparation method thereof, automobile
By pretreating and adjusting the brake discs, double-layer ultra-high-speed laser cladding technology with the base layer and hard surface layer is adopted to coordinate the speed of the rotary table and cladding head, solving the problems of particulate matter emissions caused by the brake disc wear and ultra-high-speed laser cladding technology, and achieving the preparation and production efficiency of wear-resistant and corrosion-resistant coatings.
Patent Information
- Application Number
- CN202411570943.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The particulate emissions generated by existing brake discs during wear cause harm to the human body and the environment, and the ultra-high-speed laser cladding technology has the damage to the cladding head assembly by high-power laser reflection, as well as the uneven coating and not wear-resistant.
By pre-treating and adjusting the brake discs, double-layer ultra-high-speed laser cladding technology with the base layer and hard surface layer is used to coordinate the speed of the rotary table and cladding head to ensure uniformity and efficiency of the cladding process.
The preparation of a wear-resistant and corrosion-resistant coating on the surface of the brake disc is realized, which significantly reduces particulate emissions, improves production efficiency, extends the service life of the brake disc, and reduces costs.
Smart Images

Figure CN119082727B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of brake discs, and in particular to a brake disc having a surface ultra-high-speed laser-clad wear-resistant and corrosion-resistant coating, a preparation method thereof, and an automobile. Background Art
[0002] Particulate matter emissions from vehicle braking systems have local effects and cause great harm to the human body. Unlike carbon dioxide emissions, which have a global impact on the atmosphere, particulate matter emissions generated by the friction between brake pads and brake discs during vehicle braking have local effects, that is, they cause the greatest harm to people and the environment near the emission source (such as intersections, busy roads, etc.). Studies have shown that ingesting these particles can cause physical harm such as respiratory diseases and cancer, and increase the risk of Alzheimer's disease. The latest EU Euro 7 standard has for the first time included particulate matter emissions from brake systems under control. In order to cope with this stringent standard, the most fundamental solution is to improve the wear resistance of the brake disc and reduce particulate matter emissions caused by wear from the source.
[0003] Ultra-high-speed laser cladding technology is to melt the powder and the laser beam together above the workpiece, and then evenly deposit it on the surface of the workpiece and solidify to form a protective coating. The cladding rate can be as high as 20m / min-200m / min. The coating surface quality is high and usually only requires simple grinding or polishing for application. The coating is metallurgically bonded and has high performance reliability. Compared with conventional surface protection technology, it has irreplaceable application advantages in cost, efficiency, and automation, and is particularly suitable for the preparation of wear-resistant and corrosion-resistant coatings for brake discs.
[0004] However, the high-power laser reflection that must be used in the ultra-high-speed laser cladding process can damage the cladding head components, and the coating formed by ultra-high-speed laser cladding has problems such as unevenness and poor wear resistance. Summary of the invention
[0005] The purpose of the present application is to provide a brake disc having a wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding on the surface, a preparation method thereof, and a vehicle to solve the above-mentioned problems.
[0006] To achieve the above objectives, the present application provides, in a first aspect, a method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, comprising:
[0007] Pre-treating the brake disc to obtain the brake disc to be clad;
[0008] The angle of the brake disc to be clad is adjusted so that the angle ∠1 between the surface to be clad and the axis of the cladding head and the angle ∠2 between the edge of the cladding head and the axis of the cladding head meet the conditions:
[0009] ∠1+0.5∠2<90°;
[0010] The brake disc to be clad is subjected to ultra-high speed laser cladding of a base layer and ultra-high speed laser cladding of a hard surface layer in sequence to obtain the brake disc having the ultra-high speed laser cladding wear-resistant and corrosion-resistant coating on the surface;
[0011] The ultra-high-speed laser cladding of the base layer comprises: rotating the brake disc to be clad, and performing ultra-high-speed laser cladding of the base layer from the inside to the outside to obtain a brake disc with a base layer;
[0012] The ultra-high-speed laser cladding of the hard surface layer comprises: performing ultra-high-speed laser cladding of the hard surface layer on the brake disc with the base layer from the outside to the inside to obtain the brake disc with the ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface;
[0013] During the ultra-high-speed laser cladding of the base layer and the ultra-high-speed laser cladding of the hard surface layer, ∠1 remains unchanged;
[0014] During the ultra-high-speed laser cladding of the base layer, the initial rotation speed of the brake disc to be clad satisfies:
[0015] ;
[0016] During the ultra-high-speed laser cladding of the base layer, the initial moving speed of the cladding head satisfies:
[0017] ;
[0018] During the ultra-high-speed laser cladding process of the base layer, the rotation speed of the brake disc to be clad is gradually reduced, satisfying:
[0019] ;
[0020] During the ultra-high-speed laser cladding process of the base layer, the moving speed of the cladding head gradually decreases, satisfying:
[0021] ;
[0022] During the ultra-high-speed laser cladding of the hard surface layer, the initial rotation speed of the brake disc with the base layer satisfies:
[0023] ;
[0024] During the ultra-high-speed laser cladding of the hard surface layer, the initial moving speed of the cladding head satisfies:
[0025] ;
[0026] During the ultra-high-speed laser cladding of the hard surface layer, the rotation speed of the brake disc with the base layer gradually increases, satisfying:
[0027] ;
[0028] During the ultra-high-speed laser cladding of the hard surface layer, the moving speed of the cladding head gradually increases, satisfying:
[0029] ;
[0030] Wherein, W1 is the starting rotation speed of the brake disc to be clad when preparing the brake disc with the base layer, W1 ’ is the real-time rotation speed during the preparation of the brake disc with the base layer, W2 is the starting rotation speed of the brake disc with the base layer when preparing the brake disc with the surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, and W2 ’ is the real-time rotation speed in the process of preparing the brake disc with the surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, M1 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the base layer, and M1 ’ M2 is the moving speed of the cladding head during the ultra-high-speed laser cladding of the base layer, M3 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer, and M4 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer. ’ is the moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer, V is the linear speed, L is the laser spot diameter, η is the overlap rate, D1 is the inner diameter of the brake disc, D2 is the outer diameter of the brake disc, t1 and t2 are the cladding times of the ultra-high-speed laser cladding of the base layer or the ultra-high-speed laser cladding of the hard surface layer, respectively.
[0031] Optionally, the preprocessing includes:
[0032] The surface oil stains of the brake disc are cleaned by using alcohol and / or acetone to obtain the brake disc to be clad.
[0033] Optionally, the raw material of the base layer prepared by ultra-high-speed laser cladding with a base layer includes 316L stainless steel.
[0034] Optionally, the raw materials of the hard surface layer prepared by ultra-high speed laser cladding of the hard surface layer include iron-based alloy and hard particles.
[0035] Optionally, the iron-based alloy, calculated with the total mass as 100%, includes:
[0036] C<0.02wt%, Cr16wt%-18wt%, Ni11wt%-13wt%, Mo2wt%-3wt%, Si0.5wt%-1wt%, Mn0.1wt%-0.5wt%, and the balance is Fe.
[0037] Optionally, the hard particles include one or more of tungsten carbide, titanium carbide, chromium carbide and silicon carbide.
[0038] Optionally, the method for preparing the brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating satisfies at least one of the following conditions:
[0039] A. The particle size of the iron-based alloy and / or the hard particles is 15 μm-53 μm;
[0040] B. The mass content of the hard particles in the hard surface layer is 20wt%-50wt%.
[0041] Optionally, the method for preparing the brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating satisfies at least one of the following conditions:
[0042] A. The line speed is 100m / min-200m / min;
[0043] B. The laser spot diameter is 3mm-5mm;
[0044] C. The overlap rate is 70%-90%;
[0045] D. The power of the base layer ultra-high speed laser cladding and the hard surface layer ultra-high speed laser cladding is 6000W-12000W;
[0046] E. The powder feeding rate of the cladding head is 2g / s-5g / s.
[0047] A second aspect of the present application provides a brake disc having a wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding on the surface, which is prepared by the method for preparing a brake disc having a wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding on the surface.
[0048] A third aspect of the present application provides an automobile, comprising the brake disc having the wear-resistant and corrosion-resistant coating formed by ultra-high-speed laser cladding on the surface.
[0049] Compared with the prior art, the beneficial effects of this application include:
[0050] The present application provides a method for preparing a brake disc with a wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding on the surface. First, by placing the surface to be clad at a certain angle to the axis of the cladding head, damage to the cladding head component caused by the reflection of the high-power laser that must be used in ultra-high-speed laser cladding is avoided; secondly, during ultra-high-speed laser cladding, the turntable is coordinated and regulated so that the rotation speed of the brake disc to be clad or the brake disc with a base layer and the movement speed of the cladding head change synchronously with time, thereby ensuring that the linear speed and overlap rate remain uniform during the cladding process, thereby improving the uniformity of the thickness, structure and performance of the cladding layer; then, in order to reduce the amount of deformation, the two cladding layers (base layer and hard surface layer) adopt different cladding directions; the base layer is clad from the inner diameter to the outer diameter of the brake disc to be processed. During this process, the diameter of the brake disc to be clad continues to increase. In order to keep the cladding linear speed V unchanged, the rotation speed W1 of the brake disc to be clad is ’ should be continuously reduced and the corresponding formula needs to be satisfied; at the same time, due to the rotation speed W1 of the brake disc to be clad ’ In order to keep the overlap rate of the melt track unchanged, the cladding head M1 ’ The moving speed should also be continuously reduced, and the corresponding formula needs to be satisfied; accordingly, the hard surface layer is clad from the outer diameter to the inner diameter of the brake disc with the base layer. During this process, the diameter of the brake disc with the base layer is continuously reduced. In order to keep the cladding linear speed V unchanged, the rotation speed W2 of the brake disc with the base layer ’ It should continue to increase, and another set of corresponding formulas needs to be satisfied. At the same time, as the rotation speed of the brake disc with the base layer continues to increase, in order to keep the overlap rate of the melt track unchanged, the moving speed of the cladding head M2 ’ It should also continue to increase and needs to satisfy another set of corresponding formulas.
[0051] The brake disc provided in this application has a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, and the preparation efficiency of the wear-resistant and corrosion-resistant coating of the brake disc can reach 7.2m 2 / h, reaching the highest level reported abroad so far. The cladding time of a single layer of coating on a brake disc (outer diameter 288mm, inner diameter 135mm) is less than 30s, which greatly improves production efficiency. The cladding head is at a specific angle to the brake disc, which effectively avoids damage to the optical components of the cladding equipment due to laser reflection. The powder utilization rate reaches more than 90%, which greatly reduces costs. The cladding parameters are adjusted dynamically to improve the uniformity of the coating structure. The double-layer structure bottom layer provides good corrosion resistance, and the surface layer has excellent wear resistance, which not only avoids the brake disc from being corroded in rainy, snowy and humid weather or long-term parking, resulting in unstable braking performance and affecting the safety of life and property, but also reduces corrosion and wear, greatly prolongs the service life of the brake disc, and reduces the emission of solid particles from the brake system, which is of great significance for promoting the construction of a green and environmentally friendly society.
[0052] The automobile provided by the present application reduces the emission of particulate matter caused by brake disc wear. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0054] Figure 1 A schematic diagram of the cladding process in a method for preparing a brake disc having a wear-resistant and corrosion-resistant coating on the surface by ultra-high-speed laser cladding is provided for this application;
[0055] Figure 2 A schematic diagram of a coating prepared by an existing cladding method;
[0056] Figure 3 This is a macroscopic morphology of a brake disc with a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating prepared in Example 1;
[0057] Figure 4 This is a microstructure diagram of the brake disc with a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating prepared in Example 1. DETAILED DESCRIPTION
[0058] As used herein:
[0059] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0060] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0061] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0062] In these examples, parts and percentages are by mass unless otherwise indicated.
[0063] "Mass parts" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass parts of component A are a parts and the mass parts of component B are b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass parts of all components is not limited to 100 parts.
[0064] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0065] The first aspect of the present application provides a method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, comprising:
[0066] Pre-treating the brake disc to obtain the brake disc to be clad;
[0067] The angle of the brake disc to be clad is adjusted so that the angle ∠1 between the surface to be clad and the axis of the cladding head and the angle ∠2 between the edge of the cladding head and the axis of the cladding head meet the conditions:
[0068] ∠1+0.5∠2<90°;
[0069] It should be noted that in the current actual production process, laser cladding usually places the workpiece horizontally so that the powder can be better gathered on the workpiece surface and the powder utilization rate can be improved. However, for ultra-high-speed laser cladding, the laser power is large and the laser reflection on the workpiece surface can easily cause damage to the cladding head. Therefore, Figure 1As shown, the present application deflects the workpiece at a certain angle to reduce the influence of reflection on the cladding head. At the same time, since the convergence position of the ultra-high-speed laser cladding laser and powder is above the workpiece rather than on the workpiece surface, the powder is pre-melted and reaches the workpiece surface in a semi-molten state, and can adhere to the workpiece surface. Therefore, at this deflection angle, the powder utilization rate will not be greatly affected;
[0070] The brake disc to be clad is subjected to ultra-high speed laser cladding of a base layer and ultra-high speed laser cladding of a hard surface layer in sequence to obtain the brake disc having the ultra-high speed laser cladding wear-resistant and corrosion-resistant coating on the surface;
[0071] The ultra-high-speed laser cladding of the base layer comprises: rotating the brake disc to be clad, and performing ultra-high-speed laser cladding of the base layer from the inside to the outside to obtain a brake disc with a base layer;
[0072] The ultra-high-speed laser cladding of the hard surface layer comprises: performing ultra-high-speed laser cladding of the hard surface layer on the brake disc with the base layer from the outside to the inside to obtain the brake disc with the ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface;
[0073] During the ultra-high-speed laser cladding of the base layer and the ultra-high-speed laser cladding of the hard surface layer, ∠1 remains unchanged;
[0074] During the ultra-high-speed laser cladding of the base layer, the initial rotation speed of the brake disc to be clad satisfies:
[0075] ;
[0076] During the ultra-high-speed laser cladding of the base layer, the initial moving speed of the cladding head satisfies:
[0077] ;
[0078] During the ultra-high-speed laser cladding process of the base layer, the rotation speed of the brake disc to be clad is gradually reduced, satisfying:
[0079] ;
[0080] During the ultra-high-speed laser cladding process of the base layer, the moving speed of the cladding head gradually decreases, satisfying:
[0081] ;
[0082] During the ultra-high-speed laser cladding of the hard surface layer, the initial rotation speed of the brake disc with the base layer satisfies:
[0083] ;
[0084] During the ultra-high-speed laser cladding of the hard surface layer, the initial moving speed of the cladding head satisfies:
[0085] ;
[0086] During the ultra-high-speed laser cladding of the hard surface layer, the rotation speed of the brake disc with the base layer gradually increases, satisfying:
[0087] ;
[0088] During the ultra-high-speed laser cladding of the hard surface layer, the moving speed of the cladding head gradually increases, satisfying:
[0089] ;
[0090] It should be noted that if Figure 2 As shown in the figure, the speed of the cladding head during ultra-high-speed laser cladding should be coordinated with the rotation speed of the brake disc. When preparing the base layer, the cladding head moves from the inside to the outside. If it is not adjusted, the line speed will become larger and larger, resulting in inconsistent coating thickness and performance inside and outside the brake disc. Figure 2 The coating in the middle picture is thick inside and thin outside. If you only adjust the rotation speed of the brake disc without adjusting the moving speed of the cladding head, the line speed can remain consistent, but the overlap rate between each cladding layer will change, which will also lead to inconsistent coating thickness and performance inside and outside the brake disc. Figure 2 The coating in the middle right picture is thin inside and thick outside. Similarly, when preparing the hard surface layer, the rotation speed of the cladding head and the brake disc also needs to be coordinated and adjusted according to the formula to ensure the consistency and stability of the coating thickness and performance.
[0091] Wherein, W1 is the starting rotation speed of the brake disc to be clad when preparing the brake disc with the base layer, W1 ’ is the real-time rotation speed during the preparation of the brake disc with the base layer, W2 is the starting rotation speed of the brake disc with the base layer when preparing the brake disc with the surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, and W2 ’ is the real-time rotation speed in the process of preparing the brake disc with the surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, M1 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the base layer, and M1 ’ M2 is the moving speed of the cladding head during the ultra-high-speed laser cladding of the base layer, M3 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer, and M4 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer. ’ is the moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer, V is the linear speed, L is the laser spot diameter, η is the overlap rate, D1 is the inner diameter of the brake disc, D2 is the outer diameter of the brake disc, t1 and t2 are the cladding times of the ultra-high-speed laser cladding of the base layer or the ultra-high-speed laser cladding of the hard surface layer, respectively.
[0092] It is important to understand that ultra-high-speed laser cladding changes the intersection of powder and laser beam from the workpiece surface to above the workpiece, so that about 80% of the laser energy acts directly on the powder, causing the powder to pre-melt, and then deposit on the workpiece surface to form a micro-molten pool, which rapidly solidifies to form a coating that is metallurgically bonded to the workpiece surface. In addition, due to the unique micro-molten pool characteristics of ultra-high-speed laser cladding, its heat input is low, the thermal impact on the substrate is small, and the coating surface quality is high. Usually, only simple grinding or polishing is required for application. The coating is metallurgically bonded and has high performance reliability. Compared with conventional surface protection technologies, it has irreplaceable application advantages in cost, efficiency, and automation, and is particularly suitable for the preparation of wear-resistant coatings for brake discs.
[0093] In some embodiments, the preprocessing comprises:
[0094] The surface oil stains of the brake disc are cleaned by using alcohol and / or acetone to obtain the brake disc to be clad.
[0095] In some embodiments, the raw material of the base layer prepared by ultra-high-speed laser cladding with a base layer includes 316L stainless steel.
[0096] It should be noted that the base material is stainless steel, which not only plays a role in composition transition, but also has an anti-corrosion effect, reducing the emission of Fe3O4 and other particulate matter caused by the wear of the gray cast iron matrix after corrosion.
[0097] In some embodiments, the raw materials of the hard surface layer prepared by ultra-high speed laser cladding of the hard surface layer include iron-based alloy and hard particles.
[0098] It should be noted that when the raw materials of the hard surface layer include iron-based alloy and hard particles, the iron-based alloy structure is austenite structure, and the austenite structure is a face-centered cubic structure. Since the face-centered cubic crystal has 12 slip systems, there are many spatial orientations that can be adopted during the slip process, and the slip is easy to carry out, so the austenite has good plasticity; the hard particles have the characteristics of high hardness and high wear resistance. The austenitic iron-based alloy with good plasticity in the coating plays a bonding role, fixing the hard particles in the coating without causing cracking, and the hard particles play a role in increasing strength and wear resistance. The wear resistance of the coating obtained in this way is more than 8 times that of the gray cast iron matrix, which can significantly reduce the emission of particulate matter caused by wear.
[0099] In some embodiments, the iron-based alloy, calculated with the total mass as 100%, comprises:
[0100] C<0.02wt%, Cr16wt%-18wt%, Ni11wt%-13wt%, Mo2wt%-3wt%, Si0.5wt%-1wt%, Mn0.1wt%-0.5wt%, and the balance is Fe.
[0101] Optionally, the iron-based alloy is calculated with the total mass as 100%, C can be 0.001wt%, 0.01wt%, 0.015wt% or any value <0.02wt%, Cr can be 16wt%, 17wt%, 18wt% or any value between 16wt% and 18wt%, Ni can be 11wt%, 12wt%, 13wt% or any value between 11wt% and 13wt%, Mo can be 2wt%, 2.5wt%, 3wt% or any value between 2wt% and 3wt%, Si can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt% or any value between 0.5wt% and 1wt%, Mn can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt% or any value between 0.1wt% and 0.5wt%, and the balance is Fe.
[0102] It should be noted that the iron-based alloy is an ultra-low carbon austenitic stainless steel. Austenite has a face-centered cubic structure and good toughness. On the one hand, it provides a toughening effect for the composite coating, and on the other hand, it has better bonding with hard particles (tungsten carbide, titanium carbide, chromium carbide and silicon carbide, etc.); compared with martensitic steel and duplex steel, although the martensitic stainless steel has high hardness, lattice distortion and volume collision will occur during the martensitic transformation, causing great internal stress, and cracks are prone to occur when too many ceramic particles are added; in addition, multiple temperature increases during braking will also cause the martensite to undergo tempering transformation, resulting in unstable performance; the martensite content in duplex stainless steel is about half, and it will also have similar disadvantages; and the other half of the ferrite phase has good toughness, but the strength is too low to fix the hard particles, and it has poor heat resistance and is prone to softening and deformation at high temperatures. On the one hand, the austenite phase of the alloy can be better compatible with the hard particles in the cladding layer. The austenite with good toughness can firmly fix the hard particles in the cladding layer, so that even if the hard particles are added to 30wt%, no cracks will occur. On the other hand, it also has better thermal stability, avoiding performance degradation caused by multiple temperature increases during braking.
[0103] It should also be noted that the higher content of Cr and Ni elements is to make the steel form a separate austenite phase and inhibit the formation of ferrite during the cladding process. On the other hand, these two elements can greatly improve the corrosion resistance of the alloy, prevent the brake disc from rusting in complex environments such as rain and snow, and affect the braking performance; the addition of Mo elements can improve the steel's resistance to high-temperature deformation and creep resistance, which is beneficial to improve the stability of the brake disc's emergency braking; Mo elements can also improve the steel's resistance to pitting and crevice corrosion, and further improve the environmental adaptability of the brake disc. However, when the molybdenum content is greater than 3.5%, the corrosion rate in oxidizing media (such as HNO3) will increase sharply, and Mo elements are relatively expensive, so the addition amount does not exceed 3.5%; Si elements play a role in deoxidation and slag formation during ultra-high-speed laser cladding, which can improve the performance of the cladding layer; Mn elements can form stable austenite with N and a certain amount of Ni, and manganese has a strong affinity with sulfur to form MnS, which is beneficial to eliminate the harmful effects of residual sulfur in steel.
[0104] In some embodiments, the hard particles include one or more of tungsten carbide, titanium carbide, chromium carbide, and silicon carbide.
[0105] It should be noted that hard particles include one or more of tungsten carbide, titanium carbide, chromium carbide and silicon carbide. These hard particles have the characteristics of high hardness and high wear resistance, low price and high cost performance.
[0106] In some embodiments, the method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating satisfies at least one of the following conditions:
[0107] A. The particle size of the iron-based alloy and / or the hard particles is 15 μm-53 μm;
[0108] Optionally, the particle size of the iron-based alloy and / or the hard particles may be 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 53 μm or any value between 15 μm and 53 μm;
[0109] B. The mass content of the hard particles in the hard surface layer is 20wt%-50wt%.
[0110] Optionally, the mass content of the hard particles in the hard surface layer can be 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or any value between 20wt% and 50wt%.
[0111] It should be noted that when the mass content of hard particles in the hard surface layer is 20wt%-50wt%, when the content of hard particles is less than 20%, the content is too small, and the effect of increasing strength and wear resistance is not obvious; when it exceeds 50%, the content of hard particles is too high, and the bonding phase in the coating is insufficient, which is easy to cause cracking; in addition, during the braking process, the coating expands due to heat, and the thermal expansion coefficients of the iron-based alloy and the hard particles are different. Too many hard particles will cause thermal cracks.
[0112] In some embodiments, the method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating satisfies at least one of the following conditions:
[0113] A. The line speed is 100m / min-200m / min;
[0114] Optionally, the line speed may be 100 m / min, 120 m / min, 140 m / min, 160 m / min, 180 m / min, 200 m / min or any value between 100 m / min and 200 m / min;
[0115] It should be noted that the line speed can reach 100m / min-200m / min, which is a great improvement compared to the 0.6m / min-1m / min of traditional laser cladding, thereby significantly improving the cladding efficiency.
[0116] B. The laser spot diameter is 3mm-5mm;
[0117] Optionally, the laser spot diameter may be 3 mm, 4 mm, 5 mm, or any value between 3 mm and 5 mm;
[0118] C. The overlap rate is 70%-90%;
[0119] Optionally, the overlap ratio may be 70%, 75%, 80%, 85%, 90% or any value between 70% and 90%;
[0120] D. The power of the base layer ultra-high speed laser cladding and the hard surface layer ultra-high speed laser cladding is 6000W-12000W;
[0121] Optionally, the power of the ultra-high speed laser cladding of the base layer and the ultra-high speed laser cladding of the hard surface layer may be 6000W, 7000W, 8000W, 9000W, 10000W, 11000W, 12000W or any value between 6000W and 12000W;
[0122] E. The powder feeding rate of the cladding head is 2g / s-5g / s.
[0123] Optionally, the powder feeding rate of the cladding head may be 2 g / s, 3 g / s, 4 g / s, 5 g / s or any value between 2 g / s and 5 g / s.
[0124] A second aspect of the present application provides a brake disc having a wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding on the surface, which is prepared by the method for preparing a brake disc having a wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding on the surface.
[0125] A third aspect of the present application provides an automobile, comprising the brake disc having the wear-resistant and corrosion-resistant coating formed by ultra-high-speed laser cladding on the surface.
[0126] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0127] Example 1
[0128] A first aspect of the present embodiment provides a method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, comprising:
[0129] S1: Brake disc surface pretreatment: Use alcohol or acetone to clean the oil stains on the brake disc surface to obtain the brake disc to be clad;
[0130] S2: Preparation of ultra-high-speed laser cladding iron-based composite powder for hard surface layer: 70% by mass of iron-based alloy and 30% of hard particle TiC powder are mixed in a mixer for 120 minutes. After mixing evenly, the mixture is dried at 80°C for 2 hours to obtain ultra-high-speed laser cladding iron-based composite powder for hard surface layer; wherein, the mass percentage of each element in the iron-based alloy powder is C0.01wt%, Cr16.8wt%, Ni12.1wt%, Mo2.6wt%, Si0.8wt%, Mn0.3wt%, and the remainder is Fe. The particle sizes of the base alloy powder and TiC are both 15μm-53μm.
[0131] S3: Angle adjustment: adjust the angle of the brake disc to be clad so that the angle ∠1 between the surface to be clad and the axis of the cladding head and the angle ∠2 between the edge of the cladding head and the axis of the cladding head meet the conditions: ∠1+0.5∠2<90°;
[0132] S4: performing ultra-high-speed laser cladding on the base layer and ultra-high-speed laser cladding on the hard surface layer of the brake disc to be clad in sequence, so as to obtain a brake disc with an ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface;
[0133] The base layer ultra-high speed laser cladding includes: rotating the brake disc to be clad, and performing ultra-high speed laser cladding of the base layer from the inside to the outside to obtain a brake disc with a base layer; wherein, the initial rotation speed of the brake disc to be clad at the beginning satisfies , calculated W1 = 353.68r / min; the initial moving speed of the cladding head satisfies , calculated M1 = 0.2829m / min; during the ultra-high-speed laser cladding process of the base layer, the rotation speed of the brake disc to be clad gradually decreases and meets , put the parameters into the formula and get: ; The moving speed of the cladding head gradually decreases and meets the , put the parameters into the formula and get: ;
[0134] The hard surface layer ultra-high speed laser cladding comprises: performing ultra-high speed laser cladding of the hard surface layer on the brake disc with the base layer from the outside to the inside to obtain a brake disc with an ultra-high speed laser cladding wear-resistant and corrosion-resistant coating on the surface; wherein the initial rotation speed of the brake disc with the base layer satisfies , calculated W2 = 165.79r / min, the initial moving speed of the cladding head satisfies , calculated M2 = 0.1326m / min; the rotation speed of the brake disc with the base layer gradually increases during the ultra-high-speed laser cladding process of the hard surface layer, and meets , put the parameters into the formula and get: , the moving speed of the cladding head gradually increases and satisfies , put the parameters into the formula and get: ;
[0135] The process parameters of ultra-high-speed laser cladding are: D1 is the inner diameter of the brake disc 0.135m, D2 is the outer diameter of the brake disc 0.288m, the linear speed V=150m / min, the laser spot diameter L=4mm, the overlap rate η=80%, the power of ultra-high-speed laser cladding is 9000W, and the powder feeding rate of the cladding head is 3.5g / s.
[0136] A second aspect of the present application provides a brake disc having a surface ultra-high-speed laser-clad wear-resistant and corrosion-resistant coating, which is prepared by the above-mentioned preparation method.
[0137] The macroscopic morphology of the brake disc with the wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding is shown in Figure 2. Figure 3 shown.
[0138] The coating microstructure of the brake disc with the wear-resistant and corrosion-resistant coating by ultra-high-speed laser cladding is as follows: Figure 4 shown.
[0139] After friction and wear tests, the wear resistance test results of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface were 2.75×10 -6 The wear resistance test result of the brake disc is 3.03×10 -5 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 11 times that of the brake disc.
[0140] Example 2
[0141] A first aspect of the present embodiment provides a method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, comprising:
[0142] S1: Brake disc surface pretreatment: Use alcohol or acetone to clean the oil stains on the brake disc surface to obtain the brake disc to be clad;
[0143] S2: Preparation of ultra-high-speed laser cladding iron-based composite powder for hard surface layer: 70% by mass of iron-based alloy and 20% of hard particle TiC powder are mixed in a mixer for 120 minutes. After mixing evenly, the mixture is dried at 80°C for 2 hours to obtain ultra-high-speed laser cladding iron-based composite powder for hard surface layer; wherein, the mass percentage of each element in the iron-based alloy powder is C0.01wt%, Cr16.8wt%, Ni12.1wt%, Mo2.6wt%, Si0.8wt%, Mn0.3wt%, and the remainder is Fe. The particle sizes of the base alloy powder and TiC are both 15μm-53μm.
[0144] S3: Angle adjustment: adjust the angle of the brake disc to be clad so that the angle ∠1 between the surface to be clad and the axis of the cladding head and the angle ∠2 between the edge of the cladding head and the axis of the cladding head meet the conditions: ∠1+0.5∠2<90°;
[0145] S4: performing ultra-high-speed laser cladding on the base layer and ultra-high-speed laser cladding on the hard surface layer of the brake disc to be clad in sequence, so as to obtain a brake disc with an ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface;
[0146] The base layer ultra-high speed laser cladding includes: rotating the brake disc to be clad, and performing ultra-high speed laser cladding of the base layer from the inside to the outside to obtain a brake disc with a base layer; wherein, the initial rotation speed of the brake disc to be clad at the beginning satisfies , calculated W1 = 353.68 r / min; the initial moving speed of the cladding head satisfies , calculated M1 = 0.2829m / min; during the ultra-high-speed laser cladding process of the base layer, the rotation speed of the brake disc to be clad gradually decreases and meets , put the parameters into the formula and get: / 0.0032 ; The moving speed of the cladding head gradually decreases and meets the , put the parameters into the formula and get: ;
[0147] The hard surface layer ultra-high speed laser cladding comprises: performing ultra-high speed laser cladding of the hard surface layer on the brake disc with the base layer from the outside to the inside to obtain a brake disc with an ultra-high speed laser cladding wear-resistant and corrosion-resistant coating on the surface; wherein the initial rotation speed of the brake disc with the base layer satisfies , calculated W2 = 165.79r / min, the initial moving speed of the cladding head satisfies , calculated M2 = 0.1326m / min; the rotation speed of the brake disc with the base layer gradually increases during the ultra-high-speed laser cladding process of the hard surface layer, and meets , put the parameters into the formula and get: , the moving speed of the cladding head gradually increases and satisfies , put the parameters into the formula and get: ;
[0148] The process parameters of ultra-high-speed laser cladding are: D1 is the inner diameter of the brake disc 0.135m, D2 is the outer diameter of the brake disc 0.288m, the linear speed V=150m / min, the laser spot diameter L=4mm, the overlap rate η=80%, the power of ultra-high-speed laser cladding is 9200W, and the powder feeding rate of the cladding head is 3.6g / s.
[0149] After friction and wear tests, the wear resistance test results of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface were 3.80×10 -6 The wear resistance test result of the brake disc is 3.03×10 -5 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface is 8 times that of the brake disc.
[0150] Example 3
[0151] A first aspect of the present embodiment provides a method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, comprising:
[0152] S1: Brake disc surface pretreatment: Use alcohol or acetone to clean the oil stains on the brake disc surface to obtain the brake disc to be clad;
[0153] S2: Preparation of ultra-high-speed laser cladding iron-based composite powder for hard surface layer: 70% by mass of iron-based alloy and 50% of hard particle TiC powder are mixed in a mixer for 120 minutes. After mixing evenly, the mixture is dried at 80°C for 2 hours to obtain ultra-high-speed laser cladding iron-based composite powder for hard surface layer; wherein, the mass percentage of each element in the iron-based alloy powder is C0.01wt%, Cr16.8wt%, Ni12.1wt%, Mo2.6wt%, Si0.8wt%, Mn0.3wt%, and the remainder is Fe. The particle sizes of the base alloy powder and TiC are both 15μm-53μm.
[0154] S3: Angle adjustment: adjust the angle of the brake disc to be clad so that the angle ∠1 between the surface to be clad and the axis of the cladding head and the angle ∠2 between the edge of the cladding head and the axis of the cladding head meet the conditions: ∠1+0.5∠2<90°;
[0155] S4: performing ultra-high-speed laser cladding on the base layer and ultra-high-speed laser cladding on the hard surface layer of the brake disc to be clad in sequence, so as to obtain a brake disc with an ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface;
[0156] The base layer ultra-high speed laser cladding includes: rotating the brake disc to be clad, and performing ultra-high speed laser cladding of the base layer from the inside to the outside to obtain a brake disc with a base layer; wherein, the initial rotation speed of the brake disc to be clad at the beginning satisfies , calculated W1 = 353.68 r / min; the initial moving speed of the cladding head satisfies , calculated M1 = 0.2829m / min; during the ultra-high-speed laser cladding process of the base layer, the rotation speed of the brake disc to be clad gradually decreases and meets , put the parameters into the formula and get: , the moving speed of the cladding head gradually decreases, and meets the , put the parameters into the formula and get: ;
[0157] The hard surface layer ultra-high speed laser cladding comprises: performing ultra-high speed laser cladding of the hard surface layer on the brake disc with the base layer from the outside to the inside to obtain a brake disc with an ultra-high speed laser cladding wear-resistant and corrosion-resistant coating on the surface; wherein the initial rotation speed of the brake disc with the base layer satisfies , calculated W2 = 165.79r / min, the initial moving speed of the cladding head satisfies , calculated M2 = 0.1326m / min; the rotation speed of the brake disc with the base layer gradually increases during the ultra-high-speed laser cladding process of the hard surface layer, and meets , put the parameters into the formula and get: , the moving speed of the cladding head gradually increases and satisfies , put the parameters into the formula and get: ;
[0158] The process parameters of ultra-high-speed laser cladding are: D1 is the inner diameter of the brake disc 0.135m, D2 is the outer diameter of the brake disc 0.288m, the linear speed V=150m / min, the laser spot diameter L=4mm, the overlap rate η=80%, the power of ultra-high-speed laser cladding is 8600W, and the powder feeding rate of the cladding head is 3.3g / s.
[0159] After friction and wear tests, the wear resistance test results of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface were 2.92×10 -6 The wear resistance test result of the brake disc is 3.03×10 -5 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 10.4 times that of the brake disc.
[0160] Comparative Example 1
[0161] This comparative example provides a method for preparing a brake disc with an ultra-high-speed laser cladding coating on the surface. The difference from Example 1 is that this comparative example does not perform the angle adjustment in step S3 of Example 1, so that the surface to be clad in this comparative example is perpendicular to the cladding head.
[0162] After friction and wear testing, the wear resistance of the surface ultra-high-speed laser cladding coating prepared in this comparative example is not greatly affected, but it will damage the equipment.
[0163] Comparative Example 2
[0164] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0165] The initial rotation speed of the brake disc to be clad during the base layer ultra-high-speed laser cladding does not meet the following requirements:
[0166] ;
[0167] That is, W1=400r / min.
[0168] After friction and wear test, the wear resistance test result of the ultra-high-speed laser cladding coating prepared in this comparative example is 4.46×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 6.8 times that of the brake disc.
[0169] Comparative Example 3
[0170] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0171] The initial moving speed of the cladding head during the base layer ultra-high-speed laser cladding does not meet the following requirements:
[0172] ;
[0173] That is, M1=0.35m / min.
[0174] After friction and wear test, the wear resistance test result of the ultra-high-speed laser cladding coating prepared in this comparative example is 7.73×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 3.9 times that of the brake disc.
[0175] Comparative Example 4
[0176] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0177] The rotation speed of the brake disc to be clad during the ultra-high-speed laser cladding process does not meet the following requirements:
[0178] .
[0179] After friction and wear test, the wear resistance test result of the ultra-high-speed laser cladding coating prepared in this comparative example showed that the coating performance was uneven, and the wear rate of the coating near the center was 4.81×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 6.3 times that of the brake disc; the wear rate of the coating near the outer edge is 6.31×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface is 4.8 times that of the brake disc.
[0180] Comparative Example 5
[0181] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0182] The moving speed of the cladding head during the ultra-high-speed laser cladding process does not meet the following requirements:
[0183] .
[0184] After friction and wear test, the wear resistance test result of the surface ultra-high-speed laser cladding coating prepared in this comparative example showed that the coating performance was uneven, and the wear rate of the coating near the center was 4.97×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 6.1 times that of the brake disc; the wear rate of the coating near the outer edge is 7.21×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface is 4.2 times that of the brake disc.
[0185] Comparative Example 6
[0186] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0187] The initial rotation speed of the brake disc with the base layer during ultra-high-speed laser cladding of the hard surface layer does not meet the following requirements:
[0188] ;
[0189] That is, W2=120 r / min.
[0190] After friction and wear test, the wear resistance test result of the ultra-high-speed laser cladding coating prepared in this comparative example is 5.32×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface is 5.7 times that of the brake disc.
[0191] Comparative Example 7
[0192] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0193] The initial moving speed of the cladding head during ultra-high-speed laser cladding of the hard surface layer does not meet the following requirements:
[0194] ;
[0195] That is, M2=0.1m / min.
[0196] After friction and wear test, the wear resistance test result of the ultra-high-speed laser cladding coating prepared in this comparative example is 5.94×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 5.1 times that of the brake disc.
[0197] Comparative Example 8
[0198] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0199] The rotation speed of the brake disc with the base layer during the ultra-high-speed laser cladding of the hard surface layer does not meet the following requirements:
[0200] .
[0201] After friction and wear tests, the wear resistance test results of the ultra-high-speed laser cladding coating prepared in this comparative example showed that the coating performance was uneven, and the wear rate of the coating near the center was 5.51×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 5.5 times that of the brake disc; the wear rate of the coating near the outer edge is 4.52×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface is 6.7 times that of the brake disc.
[0202] Comparative Example 9
[0203] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that:
[0204] The moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer does not meet the following requirements:
[0205] .
[0206] After friction and wear tests, the wear resistance test results of the ultra-high-speed laser cladding coating prepared in this comparative example showed that the coating performance was uneven, and the wear rate of the coating near the center was 5.22×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 5.8 times that of the brake disc; the wear rate of the coating near the outer edge is 4.27×10 -6 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating is 7.1 times that of the brake disc.
[0207] Comparative Example 10
[0208] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface. The difference from Example 1 is that the raw material of the hard surface layer in this comparative example is only an iron-based alloy.
[0209] After friction and wear test, the wear resistance test result of the ultra-high-speed laser cladding coating prepared in this comparative example is that the coating wear rate is 1.59×10 -5 The wear resistance of the brake disc with ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface is 1.9 times that of the brake disc.
[0210] Comparative Example 11
[0211] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface. The difference from Example 1 is that the raw material of the hard surface layer in this comparative example is only hard particles.
[0212] After friction and wear testing, the wear resistance test result of the surface ultra-high-speed laser cladding coating prepared in this comparative example showed that only hard particles could not be clad and formed.
[0213] Comparative Example 12
[0214] This comparative example provides a method for preparing a brake disc having an ultra-high-speed laser cladding coating on the surface, which is different from Example 1 in that the mass content of hard particles in the hard surface layer raw material of this comparative example is 55wt%.
[0215] After friction and wear testing, the wear resistance test result of the surface ultra-high-speed laser cladding coating prepared in this comparative example was that macro cracks appeared in the hard surface layer and the cladding layer could not be used.
[0216] Comparative Example 13
[0217] This comparative example provides a method for preparing a brake disc having a surface ultra-high-speed laser cladding coating, which is different from Example 1 in that the iron-based alloy in this comparative example, calculated with the total mass as 100%, includes:
[0218] C0.05wt%, Cr15wt%, Ni10wt%, Mo5wt%, Si2wt%, Mn0.5wt%, and the balance is Fe.
[0219] After friction and wear testing, the wear resistance test result of the surface ultra-high-speed laser cladding coating prepared in this comparative example was that microcracks appeared in the cladding layer and it could not be used.
[0220] Friction and wear test: reciprocating friction and wear, the contact mode is plane, the grinding pair is SiN ball with a diameter of 7.938mm, the load is 120N, the time is 30min, and the reciprocating speed of the steel ball is 10 mm / s).
[0221] It can be seen from the above embodiments and comparative examples that the cladding at a certain angle adopted in the present invention can protect the optical components of the equipment from damage while ensuring the performance of the cladding layer. The double-layer structure of the base layer and the hard surface layer can achieve the effect of corrosion resistance and wear resistance. Through the dynamic coordinated adjustment of the rotation speed and the moving speed of the cladding head, the performance of the cladding layer can be made uniform, thereby ensuring the stability of the brake disc performance. The wear resistance of the brake disc after cladding can reach 11 times that of the unclad brake disc.
[0222] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0223] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a brake disc having a wear-resistant and corrosion-resistant coating on the surface by ultra-high-speed laser cladding, characterized in that: include: Pre-treating the brake disc to obtain the brake disc to be clad; The angle of the brake disc to be clad is adjusted so that the angle ∠1 between the surface to be clad and the axis of the cladding head and the angle ∠2 between the edge of the cladding head and the axis of the cladding head meet the conditions: ∠1+0.5∠2<90°; The brake disc to be clad is subjected to ultra-high speed laser cladding of a base layer and ultra-high speed laser cladding of a hard surface layer in sequence to obtain the brake disc having the ultra-high speed laser cladding wear-resistant and corrosion-resistant coating on the surface; The ultra-high-speed laser cladding of the base layer comprises: rotating the brake disc to be clad, and performing ultra-high-speed laser cladding of the base layer from the inside to the outside to obtain a brake disc with a base layer; The ultra-high-speed laser cladding of the hard surface layer comprises: performing ultra-high-speed laser cladding of the hard surface layer on the brake disc with the base layer from the outside to the inside to obtain the brake disc with the ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating on the surface; During the ultra-high-speed laser cladding of the base layer and the ultra-high-speed laser cladding of the hard surface layer, ∠1 remains unchanged; During the ultra-high-speed laser cladding of the base layer, the initial rotation speed of the brake disc to be clad satisfies: ; During the ultra-high-speed laser cladding of the base layer, the initial moving speed of the cladding head satisfies: ; During the ultra-high-speed laser cladding process of the base layer, the rotation speed of the brake disc to be clad is gradually reduced, satisfying: ; During the ultra-high-speed laser cladding process of the base layer, the moving speed of the cladding head gradually decreases, satisfying: ; During the ultra-high-speed laser cladding of the hard surface layer, the initial rotation speed of the brake disc with the base layer satisfies: ; During the ultra-high-speed laser cladding of the hard surface layer, the initial moving speed of the cladding head satisfies: ; During the ultra-high-speed laser cladding of the hard surface layer, the rotation speed of the brake disc with the base layer gradually increases, satisfying: ; During the ultra-high-speed laser cladding of the hard surface layer, the moving speed of the cladding head gradually increases, satisfying: ; Wherein, W1 is the starting rotation speed of the brake disc to be clad when preparing the brake disc with the base layer, in r / min; W1 ’ W2 is the real-time rotation speed during the preparation of the brake disc with the base layer, in r / min; W2 is the starting rotation speed of the brake disc with the base layer when preparing the brake disc with the surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, in r / min; W2 ’ is the real-time rotation speed in the process of preparing the brake disc with the surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating, in r / min; M1 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the base layer, in m / min; M1 ’ M2 is the moving speed of the cladding head during the ultra-high-speed laser cladding of the base layer, in m / min; M3 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer, in m / min; M4 is the starting moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer, in m / min; ’ is the moving speed of the cladding head during the ultra-high-speed laser cladding of the hard surface layer, in m / min; V is the linear speed, in m / min; L is the laser spot diameter, in m; η is the overlap rate, D1 is the inner diameter of the brake disc, in m; D2 is the outer diameter of the brake disc, in m; t1 and t2 are the cladding times of the ultra-high-speed laser cladding of the base layer or the ultra-high-speed laser cladding of the hard surface layer, in min, respectively.
2. The method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The pre-processing comprises: The surface oil stains of the brake disc are cleaned by using alcohol and / or acetone to obtain the brake disc to be clad.
3. The method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The raw material of the base layer prepared by the base layer ultra-high-speed laser cladding includes 316L stainless steel.
4. The method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating according to claim 1, characterized in that: The raw materials of the hard surface layer prepared by ultra-high-speed laser cladding of the hard surface layer include iron-based alloy and hard particles.
5. The method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating according to claim 4, characterized in that: The iron-based alloy, calculated with the total mass as 100%, includes: C<0.02wt%, Cr16wt%-18wt%, Ni11wt%-13wt%, Mo2wt%-3wt%, Si0.5wt%-1wt%, Mn0.1wt%-0.5wt%, and the balance is Fe.
6. The method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating according to claim 4, characterized in that: The hard particles include one or more of tungsten carbide, titanium carbide, chromium carbide and silicon carbide.
7. The method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating according to claim 4, characterized in that: At least one of the following conditions is met: A. The particle size of the iron-based alloy and / or the hard particles is 15 μm-53 μm; B. The mass content of the hard particles in the hard surface layer is 20wt%-50wt%.
8. The method for preparing a brake disc having a surface ultra-high-speed laser cladding wear-resistant and corrosion-resistant coating according to any one of claims 1 to 7, characterized in that: At least one of the following conditions is met: A. The line speed is 100m / min-200m / min; B. The laser spot diameter is 3mm-5mm; C. The overlap rate is 70%-90%; D. The power of the base layer ultra-high speed laser cladding and the hard surface layer ultra-high speed laser cladding is 6000W-12000W; E. The powder feeding rate of the cladding head is 2g / s-5g / s.
Citation Information
Patent Citations
Method and equipment for manufacturing high-performance disc parts
CN114507855A